Role of amino acids in halotolerant Aspergillus repens - U. P. Kelavkar; H. S. Chhatpar (Fungal Genetics Reports, 1992)
Attempts have been made earlier to understand the mechanisms of osmoregulation and the ability ot adapt to fluctuations in the external osmolarity (Ben-Amotz and Avron 1983. Ann. Rev. Microbiol. 37:95-119, Csonka 1989. Microbiol. Rev. 53:121-147). Various strategies have been adopted by the cells in order to survive and proliferate in the presence of reduced water activity, including accumulation of carbohydrates. amino acids and quaternary ammonium compounds (Measures 1975. Nature 257:398-400, Brown et al. 1972. J. Gen. Microbiol. 72:589-591, Dannibier et al. 1988. Arch. Microbiol. 150:348-357). In the present study, attempts were made to investigate the role of amino acids that accumulate intracellularly in halotolerant Aspergillus repens under salt stress condition.